Efficient chaff-aided obfuscation in resource constrained environments - Ciftcioglu, Ertugrul N.; Hardy, Rommie L.; Scott, Lisa M.; Chan, Kevin S. (MILCOM IEEE Military Communications Conference, 2017)
This work considers the use of obfuscation against a global eavesdropper in a resource-constrained environment. We assume a network where network traffic (queries) is not always present on the network but is stochastic in nature. Even if the traffic is encrypted and the payload of packets are secure, under the threat of a passive adversary, activity over the links might be subjected to traffic analysis through network monitoring. To counter leakage of contextual information to such an adversary, the operator is able to mask the presence of traffic over a link if it normalizes link activity by adding chaffs. However, adding chaff to all links all the time might consume too much of the operators resources. Similarly, the adversary may try to eavesdrop over all links to observe any traffic pattern change to perform analysis. However, due to the bursty nature of link traffic and the high cost of operating and collecting information from all eavesdropping units, the adversary might not want or be able to operate all eavesdroppers simultaneously. The possibility that links may not be subject to eavesdropping might lead the operator to being more lenient in the use of chaff packets. If we incorporate operational (e.g. cost of chaffs) plus contextual (obfuscation score) costs as payoffs, we highlight the existence of a mixed strategy equilibria for employing chaff. The goal of this paper is to construct a two-player game that characterize the proper amount of chaff deployment given varying eavesdropping strategies. Several basic network examples are provided to demonstrate the effectiveness of this mixed strategy which can be extended into larger scenarios. Our analysis uncovers counter-intuitive insights on the areas of the network for the adversary to eavesdrop. We also identify conditions for existence of pure strategy Nash Equilibrium for various settings like a two-hop network.